The Growing season - "Olsen, Violet." (New York)
"Eleven-year-old Marie, living on her family's farm in Iowa, learns to face and overcome Depression poverty, family problems, and her own childhood fears."
Keywords: FARM LIFE -- FICTION.;IOWA -- FICTION.;DEPRESSIONS -- 1929 -- FICTION.;DANISH AMERICANS -- FICTION